Improving produce safety by reducing pathogen load in soil using cover crops and developing food safety educational resources for produce growers - Zhao, Yeqi (Kansas State University, 2022)
Fresh produce (commonly consumed raw) has been continually associated with multiple foodborne disease outbreaks, which cause both health concerns and economic losses. Agricultural water and contaminated soil are suspected as common causative agents for recent produce-related foodborne illness outbreaks, which brought fresh produce safety to the forefront of public attention. New federal regulations by the U.S. Food and Drug Administration (FDA) as part of the FDA Food Safety Modernization Act (FSMA) established the Produce Safety Rule (PSR), which defined scientific criteria for growing, harvesting, storing, and packaging fresh produce. The PSR provides requirements on treating soil amendments and criteria for safer use of agricultural water. There are several soil and water treatment methods and practices to reduce human pathogens in fresh produce. Specifically, for contaminated soils, cover crops have been recently explored for antimicrobial application in produce production, in addition to their soil health benefits. Cover crops are plants seeded before or after the growing season to improve soil health, increase water availability, reduce weed pressure, and prevent erosion. Cover crops also produce various antimicrobial secondary metabolites (i.e., glucosinolates, quercetin), yet the role of cover crops in moderating the population of human pathogens in the soil has rarely been investigated. However, with regards to the microbial quality of agricultural water, Kansas State University and University of Missouri Extension educators have been providing free water testing, training and information on agricultural water microbial quality to help produce growers reduce microbial risks from ag water sources. The goal of this thesis is to study cover crops as potential antimicrobial interventions and understand grower needs to improve food safety measures and practices on a fresh produce farm. To achieve this goal, there are two specific objectives: (1) soil treatment: determine the antimicrobial potential of three cover crop species to reduce the population of pathogenic soil microbiota which can minimize the possibility of cross-contamination of produce from agricultural soil; (2) agricultural water: determine knowledge gaps among Kansas and Missouri produce growers related to agricultural water quality and best practices and develop agricultural water safety handouts to improve growers’ knowledge. To complete the first part of this thesis, whole-plant samples of 4-week-old mustard greens (Brassica juncea, ‘Kodiak’), sun hemp (Crotalaria juncea), or buckwheat (Fagopyrum esculentum) were chopped and mixed into autoclaved farm soil and inoculated with 7-logs of rifampicin-resistant generic Escherichia coli (E. coli). The surviving microbial population on days 0, 4, 10, 15, 20, 30, and 40 was enumerated using an agar-based methodology. All three cover crops significantly reduced the population of generic E. coli compared to the control (p < 0.0001); buckwheat resulted in the highest reduction (3.92 log CFU/g). An inhibitory effect on microbial growth was also observed in soils containing mustard greens (p < 0.0001) and sunn hemp (p < 0.0001). This study provides evidence for the bactericidal and bacteriostatic effects of cover crops. More information regarding the crops’ secondary metabolite profile and potential as a soil bio-mitigation strategy to improve on-farm produce safety is warranted. For objective 2, a survey was developed and administered to determine future extension outputs and activities to encourage growers to improve their practices related to water quality. The survey was distributed to Kansas and Missouri produce growers attending in-person or online produce safety-related events in late 2020 and early 2021. Also, it was distributed through email lists of produce growers from both states. Survey results (n = 101) indicate that 13.9% of the respondents tested their water for generic Escherichia coli (E. coli) more than once a year, while 38.6% of the participants have never tested their water. Approximately half (59.3%) of respondents indicated they use municipal water for postharvest uses, while 6.7% indicated the use of untreated surface water for postharvest activities. Due to the concern of potential water contamination risks, researchers suggest that further training and educational resources would help growers improve practices related to water quality and produce safety. Three handouts were developed to help growers better understand the current FSMA PSR water quality requirements (under consideration for further modifications) and best practices. These handouts include the following: (1) “New modified FSMA PSR agricultural water requirement proposal” handout summarizes the major modifications of the latest water proposal published in 2021; (2) “How to interpret water results” handout provides information to identify agricultural water uses and microbial safety criteria and best practices; and (3) “Back flush water fact sheet” discusses the hazards from back flush water and potential solutions. In conclusion, this thesis focuses on improving fresh produce safety by minimizing the cross-contamination happening in agricultural soil and water. The reduction of microbial populations in the first part of the thesis demonstrated the potential of cover crops to be used as a sustainable antimicrobial treatment method for contaminated soil. Meanwhile, the survey results show produce growers have a basic awareness of agricultural water practices, but the safety of those practices can still be strengthened. The publication of relevant handouts can improve growers' knowledge and help them better comply with the latest regulations.
Keywords: Produce safety rule; Extension education; Agricultural water; Soil amendment